Intel Trusted Execution Technology for Server Platforms: A Guide to More Secure Datacenters - William Futral (Apress, 2013)
Intel® Trusted Execution Technology (Intel TXT) is a new security technology that started appearing on Intel server platforms in 2010. This book explains Intel Trusted Execution Technology for Servers, its purpose, application, advantages, and limitations. This book guides the server administrator / datacenter manager in enabling the technology as well as establishing a launch control policy that he can use to customize the server's boot process to fit the datacenter's requirements. This book explains how the OS (typically a Virtual Machine Monitor or Hypervisor) and supporting software can build on the secure facilities afforded by Intel TXT to provide additional security features and functions. It provides examples how the datacenter can create and use trusted pools.